Method of big phase shift unambiquity determination - Бабак, В. П.; Куц, Ю. В. (Proceedings of National Aviation University (archive), 2003)
The application of the multifrequency method of the unambiquity avoidence during the process of big phase shift measuring on the basis of the numerical theory has been provide. The conditions have been discussed to bring the task of unambiquity avoidence to the reconstruction of the whole number which is presented by its deduction according to the definite module system, and to check the accuracy of unambiquity avoidence